Some Remarks on the Ivy Leaf Lamp Found in Ptolemais - Maria Jaworska (Ksiegarnia Akademicka Publishing, 2019)
During the Polish excavations in Ptolemais (Libya), a unique terracotta lamp top of the Cretan Ivy Leaf type was found. It is one of only few known specimens of that kind found on the site. The article provides a brief discussion on the Cretan influences seen in the lychnological material found in Ptolemais. It also draws attention to the problem of studying the relations between the two parts of the Roman province Crete and Cyrenaica.